A world without digital inclusivity - Neor Tiku (The Journal of Intelligence, Conflict and Warfare, 2021)
On April 23, 2021, Neor Tiku presented A world without digital inclusivity: What it means to securitize technology at the 2021 CASIS Generation Z Congress. This presentation was followed by a group panel question and answer session, whereby congress attendees were provided with an opportunity to engage in discussion with Mr. Tiku. Primary discussion topics included understanding the digital divide in Canada and possible measures to close this gap, inclusive of Canadian approaches taken to potentially close this gap in access.